The Better You Are the Stronger It Makes You : Evidence on the Asymmetric Impact of Liberalization - Iacovone, Leonardo (2012)
This paper studies how liberalization affects productivity growth using micro-level plant data. While previous studies have already shown the existence of a positive relationship between competition and economic performance, the novelty of this paper is that it analyzes not only the average impact of liberalization, but also goes "beyond the average" and shows how the liberalization can affect dissimilar plants in a different way. The author first develops a model which predicts that, while the impact of liberalization on productivity growth is positive "on average", more advanced firms tend to benefit more. In fact, liberalization generates two competing effects: on one side it spurs more innovative efforts because of the increased entry threat by foreign competitors, on the other side, enhanced competition curtails expected profits and reduces the funds available to finance innovative activities. The pro-competitive effect is weaker for less advanced firms as for them it is harder to catch-up with the "technology frontier". These predictions are then tested focusing on Mexican plants during the NAFTA liberalization. The results show that a 1 percent reduction in tariffs spurred productivity growth between 4 and 8 percent on average. However, for backward firms this effect is much weaker if not close to zero, otherwise for more advanced ones this effect is stronger with productivity growing between 11 and 13 percent. Consistent with the theoretical model the results are stronger in those sectors where the scope for innovative activities is more pronounced. These results are particularly important for policy makers because they suggest that while increasing competition may be good in spurring average productivity, it is also true that this effect does not hold for all type of firms, in particular more backward firms may need some complementary support policy to upgrade their capacities and keep up with the more competitive environment.